Adiponectin Enhances B-Cell Proliferation and Differentiation via Activation of Akt1/STAT3 and Exacerbates Collagen-Induced Arthritis - Che, Nan; Sun, Xiaoxuan; Gu, Lei; Wang, Xiaohui; Shi, Jingjing; Sun, Yi; Xu, Lingxiao; Liu, Rui; Wang, Junke; Zhu, Fengyi; Peng, Na; Xiao, Fan; et al. (Frontiers in Immunology, 2021)
Although B cells have been shown to contribute to the pathogenesis of rheumatoid arthritis (RA), the precise role of B cells in RA needs to be explored further. Our previous studies have revealed that adiponectin (AD) is expressed at high levels in inflamed synovial joint tissues, and its expression is closely correlated with progressive bone erosion in patients with RA. In this study, we investigated the possible role of AD in B cell proliferation and differentiation. We found that AD stimulation could induce B cell proliferation and differentiation in cell culture. Notably, local intraarticular injection of AD promoted B cell expansion in joint tissues and exacerbated arthritis in mice with collagen-induced arthritis (CIA). Mechanistically, AD induced the activation of PI3K/Akt1 and STAT3 and promoted the proliferation and differentiation of B cells. Moreover, STAT3 bound to the promoter of the Blimp-1 gene, upregulated Blimp-1 expression at the transcriptional level, and promoted B cell differentiation. Collectively, we observed that AD exacerbated CIA by enhancing B cell proliferation and differentiation mediated by the PI3K/Akt1/STAT3 axis.